2003
DOI: 10.1093/ije/dyg023
|View full text |Cite
|
Sign up to set email alerts
|

Stability of plasma analytes after delayed separation of whole blood: implications for epidemiological studies

Abstract: A wide range of important analytes, including lipids, change by only a few per cent in whole blood during storage at room temperature for several days. Mailed transport of whole blood samples may, therefore, be a simple and cost-effective option for large-scale epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
79
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 6 publications
5
79
2
3
Order By: Relevance
“…The short-term storage (4 years) revealed non-significant differences for most components. Although the Janus samples were exposed for prolonged clot-time at 4°C for up to 28 h, studies have reported that a similar sample handling had small or negligible impact on cholesterol and lipoproteins [9][10][11][12][13], and the hormones LH, PRL, FSH and FT4 [12,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The short-term storage (4 years) revealed non-significant differences for most components. Although the Janus samples were exposed for prolonged clot-time at 4°C for up to 28 h, studies have reported that a similar sample handling had small or negligible impact on cholesterol and lipoproteins [9][10][11][12][13], and the hormones LH, PRL, FSH and FT4 [12,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Some analytical issues related to nutritional biomarker measurements were previously discussed in a series of papers (Hankinson et al, 1989;Key et al, 1996;Comstock et al, 2001;Clark et al, 2003;Clark et al, 2004). These papers focused on analytical issues related to analysis of only a few markers in whole blood or sera samples.…”
Section: Introductionmentioning
confidence: 99%
“…Specification of storage modality of samples analyzed is very important since it is known that creatine, over time and changing pH of medium, varies its concentration transforming itself into creatinine [15,17]. Our plasma creatine and GAA reference values are determined by large group of control subject allowing us to obtain three age-related ranges, clearly indicating storage modality of samples.…”
Section: Discussionmentioning
confidence: 99%